EVALUATION OF REMAINING MATERIALS FOR RAILWAY CONSTRUCTION PROJECT - Atiko Putri, Ni'mah Izati; Malaiholo, David; Astuti, Septiana Widi (Asosiasi Peneliti Sriwijaya, 2024)
This study investigates residual materials in the railway construction project. The Fishbone Diagram method identifies factors causing material waste, while the Waste Hierarchy guides material management by contractors. The remaining materials include spun piles, ballast stopper cover plates, wiremesh, concrete pad anchoring systems, and PVC pipes. The quantities are 1306.5 meters of spun pile, 86 ballast stopper cover plates, 4 wire mesh sheets, and a concrete pad anchoring system with 160 e-clips, 160 insulators, 80 rail pads, and 7 pieces of 6-inch diameter PVC pipe, along with 13 pieces of 8-inch diameter PVC pipe. The largest remaining material costs come from spun piles. Fishbone Diagram analysis categorizes the construction material waste as direct waste. Poor cutting conditions cause waste in spun piles, PVC pipes, and wire mesh. Waste Hierarchy suggests reusing materials where possible, with leftover PVC pipes suitable for recycling into pots or home decorations. Disposal is necessary for non-reusable or non-recyclable materials.